ATTITUDES OF STAKEHOLDERS TOWARD THE INCLUSION AND TEACHING OF SEXUALITY EDUCATION IN NDOLA URBAN SECONDARY SCHOOLS OF COPPERBELT PROVINCE, ZAMBIA - Adebayo, Awoniyi Samuel; Exilder, Chuunga Chilekwa (European Scientific Journal, ESJ, 2014)
This study investigated the attitudes of stakeholders toward school sexuality education in Ndola Urban District Secondary Schools. The descriptive qualitative research design was adopted for the study. Eight secondary schools, 377 teachers and 5, 737 pupils formed the population for the study. The sample for the study consisted of ninety (90) teachers, ninety (90) pupils and ninety (90) parents (with pupils in the schools) who were randomly selected. The instrument used for data collection was a close ended questionnaire of the five point Likert scale designed by the researcher. The instrument was both face and content validated by experts at Solusi University. To test the reliability of the instrument, a pilot study was carried out in two schools in the neighbouring Masaiti District using 40 respondents. The reliability of the instrument was determined using the Cronbach’s alpha reliability method and a reliability coefficient of 0.840 was obtained. Data collected was coded and analysed using the Statistical Package for Social Sciences. Descriptive statistics and the one-way analysis of variance were employed for data analysis. The result of the study revealed that the stakeholders (teachers, pupils and parents) in general had positive attitude toward the inclusion of sexuality education in the school curriculum. However, the teachers, pupils and parents had a negative attitude on the inclusion of topics like sexual pleasure and enjoyment, homosexuality as well as premarital sex as topics in the curriculum. There existed significant differences in the attitudes of stakeholders toward the inclusion of sexuality education in the curriculum as well as on the role of sexuality education in adolescent issues as revealed by the analysis of variance. The multiple comparisons showed that there existed significant differences in the attitudes of teachers and parents as well as in the attitudes of pupils and parents as it related to the role of sexuality education in adolescent issues an indication that pupils and teachers were in better agreement than their parents counterparts. In view of the positive attitude of stakeholders toward the inclusion and teaching of sexuality education in the school curriculum coupled with its benefits to adolescent sexual issues, it was recommended that sex education should be compulsory in schools.